The reaction ⁴He(γ,p)³H, caused by polarized photons in the giant resonance range - Peretiatko, A.A.; Murtazin, R.T.; Khodyachikh, A.F. (Вопросы атомной науки и техники, 2019)
The reaction of ⁴He(γ,p)³H in the range of giant resonance was studied by a streamer chamber method in a magnetic ﬁeld irradiated with polarized photons obtained by plane channeling of electrons by a diamond crystal. The angular and energetic dependences of the asymmetry of the cross section have been measured. The results are explained by the mechanism of direct knock out of nucleons. За методом стримерної камери в магнитному полі, що опромінювалась поляризованими фотонами, які отримано при площинному каналюванні електронів кристалом діаманта, досліджено реакцію ⁴He(γ,p)³H в області її гігантського резонансу. Виміряно кутову та енергетичну залежності асіметрії перерізу. Результати пояснюються механізмом прямого вибивання нуклонів. Методом стримерной камеры в магнитном поле, облученной поляризованными фотонами, полученными при плоскостном каналировании электронов кристаллом алмаза, исследована реакция ⁴He(γ,p)³H в области ее гигантского резонанса. Измерены угловая и энергетическая зависимости асимметрии сечения. Результаты объясняются механизмом прямого выбивания нуклонов.